2002
DOI: 10.1172/jci15777
|View full text |Cite
|
Sign up to set email alerts
|

Misfolded proteinase K–resistant hyperphosphorylated α-synuclein in aged transgenic mice with locomotor deterioration and in human α-synucleinopathies

Abstract: The pathological modifications of α-synuclein (αS) in Parkinson disease and related diseases are poorly understood. We have detected misfolded αS in situ based on the proteinase K resistance (PK resistance) of αS fibrils, and using specific antibodies against S129-phosphorylated αS as well as oxidized αS. Unexpectedly massive neuritic pathology was found in affected human brain regions, in addition to classical αS pathology. PK resistance and abnormal phosphorylation of αS developed with increasing age in (Thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
238
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(267 citation statements)
references
References 49 publications
24
238
0
5
Order By: Relevance
“…This severe clinical phenotype occurs earlier in the disease in the homozygous transgenic mice, whereas in the heterozygous is present only in later stages Lee et al, 2002;Gomez-Isla et al, 2003), indicating that increased levels of mutant a-Syn, expressed in homozygous transgenic mice are crucial to drive nerve fibers' degeneration and motoneurons disease. Similar pathological alterations were detected in human A30P a-Syn transgenic mice that develop a neurodegenerative phenotype with age-dependent penetrance, characterized by rapidly deteriorating motor performance, with hind limbs paralysis (Neumann et al, 2002;Fournier et al, 2009). In both transgenic models these pathological features develop in absence or before degeneration of nigral dopaminergic neurons.…”
Section: Peripheral Nerve Degeneration and Muscle Denervation In Transupporting
confidence: 60%
“…This severe clinical phenotype occurs earlier in the disease in the homozygous transgenic mice, whereas in the heterozygous is present only in later stages Lee et al, 2002;Gomez-Isla et al, 2003), indicating that increased levels of mutant a-Syn, expressed in homozygous transgenic mice are crucial to drive nerve fibers' degeneration and motoneurons disease. Similar pathological alterations were detected in human A30P a-Syn transgenic mice that develop a neurodegenerative phenotype with age-dependent penetrance, characterized by rapidly deteriorating motor performance, with hind limbs paralysis (Neumann et al, 2002;Fournier et al, 2009). In both transgenic models these pathological features develop in absence or before degeneration of nigral dopaminergic neurons.…”
Section: Peripheral Nerve Degeneration and Muscle Denervation In Transupporting
confidence: 60%
“…These models exhibited abnormal accumulation of aSyn protein in neurons and altered behavioral phenotypes. However, these animals hardly displayed progressive loss of DA neurons in the SNpc [4,[85][86][87][88][89][90][91][92][93][94][95]. Among these, Masliah et al (2000) showed inclusion formation and significant reduction of DA nerve terminals in the striatum of the aSyn-transgenic mice [85].…”
Section: Neuronal Loss Induced By Asyn Overexpression In Vivomentioning
confidence: 99%
“…In studies using the mPrP promoter and contrary to earlier reports, no abnormal a-synuclein accumulation or behavioural deficits were detected in mice overexpressing the WT human protein. Transgenic mice overexpressing the A30P mutant a-synuclein driven by the Thy1 promoter also develop many of the salient features of LB disease such as proteinase Kresistance, neuritic pathology and formation of some argyrophilic and thioflavin S-positive a-synuclein inclusions with increasing age [45]. It is of interest that although mPrP but not Thy1 promoter drives high expression of the transgene in neurones of the substantia nigra (SN), as revealed by in situ hybridisation [44], the tyrosine hydroxylase (TH)-positive neurones of the SN in the mPrP-driven transgenic mice were completely spared from asynuclein aggregates or other deficits such as loss of striatal dopamine or dopamine transporter [43,44].…”
Section: Effect Of Genetic Modificationsmentioning
confidence: 99%